Effect of light curing modes on mechanical properties of direct and indirect composites - Catelan, Anderson; Santo, Márcia Regina Do Espírito [UNESP]; Menegazzo, Lívia Maluf [UNESP]; Moraes, João Carlos Silos [UNESP]; Santos, Paulo Henrique dos [UNESP] (My University, 2013)
Objective. To evaluate the degree of conversion (DC), flexural strength (FS) and Knoop microhardness (KHN) of direct and indirect composite resins polymerized with different curing systems. Materials and methods. Specimens of direct (Z250, 3M/Espe) and indirect (Sinfony, 3M/Espe) restorative materials were made and polymerized using two light curing units: XL2500 (3M/Espe) and Visio system (3M/Espe). Absorption spectra of both composites were obtained on a FTIR spectrometer in order to calculate the DC. FS was evaluated in a universal testing machine and surface microhardness was performed in a microhardness tester (50gf/15s). DC, FS and KHN data were submitted to two-way ANOVA and Tukey's test (α = 0.05). Results. Z250 showed higher DC, FS and KHN compared with Sinfony when the polymerization was carried out with XL2500 (p < 0.05). However, there is no statistical difference in DC between the materials when Visio was used (p > 0.05). Visio showed higher DC and KHN for Z250 and Sinfony than the values obtained using XL2500 light curing (p < 0.05). For FS, no significant difference between curing units was found (p > 0.05). Conclusion. Even though the Visio system could increase DC and KHN for some direct and indirect composites, compared with the conventional halogen curing unit, a high number of monomers did not undergo conversion during the polymerization. © 2013 Informa Healthcare.
Keywords: Composite resins; Degree of conversion; Flexural strength; Hardness; Mechanical properties